PENERAPAN PROJECT BASED LEARNING BERBASIS KOLABORATIF UNTUK MENINGKATKAN HASIL BELAJAR PESERTA DIDIK PADA PEMBELAJARAN TEMA 3 POTENSI EKONOMI LINGKUNGAN KELAS VII DI SMP NEGERI 1 RENGEL - Syahroni, Syahroni; Nafi, Abdurrohman; Bangsa Relasari, Tri; Perdana Prasetya, Sukma; Pujiwidada, Hariyanta (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
The Merdeka Curriculum is a curriculum that provides freedom for teachers to choose various learning models to be applied in the classroom and can be adjusted to the learning needs and interests of the students. One of them is the Project Based Learning (PjBL)model. Project Based Learning (PjBL) is a learning activity in the form of creating products or services that are used as a means to master competencies. This study aims to improve student learning outcomes through a collaborative-based Project Based Learning (PjBL) model in learning Theme 3 Economic Potential of the Environment for seventh-grade students at SMP Negeri 1 Rengel. This research is a classroom action research conducted through two learning cycles. The subjects of this study are all students in class VII C, totaling 32 students. The variables in this study consist of the independent variable, which is the Project Based Learning (PjBL) model, and the dependent variable, which is the student learning outcomes. The data collection technique in this study uses a test technique. Data analysis techniques use simple statistical techniques in the form of percentages of student learning outcomes between the pre-cycle and after the cycle. Based on the results of this study, it can be concluded that learning using the Project Based Learning (PjBL) model can improve student learning outcomes. In cycle I, 17 students (53%) completed the cycle, and 15 students (47%) did not. In cycle II, 28 students (88%) completed the cycle, and 4 (12%) did not. Thus, after conducting cycle II, student learning outcomes increased by 35%.